Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Mengikuti Uskad - Liana Susanto; Yanti Yanti; Viriany Viriany; Henny Wirianata (Jurnal Bina Akuntansi, 2020)
Abstract: The purpose of this research was to obtained empirical evidence about the influence of subjective norms, behavioral control, and expectations for the results of the interest of accounting students to take USKAD. Samples were taken by purposive sampling technique. Data were obtained through questionnaires. Respondents in this research were 2015 and 2016 Faculty of Economics Tarumanagara University accounting students. Data from the questionnaires were processed using the Smart-PLS program version 3.2.8. The results of the research showed subjective norms, behavioral control, and expectations for the results have significant influence towards the interest of accounting students to take USKAD.